PERAN HALAQAH DALAM INTERNALISASI AKHLAK MAHASISWA LDK AL-IZZAH UIN SUMATERA UTARA - Patma Aulia; Nur Citra Naadirah Br Tarigan; Nur Zannah; Zainal Abidin (Islamijah: Journal of Islamic Social Sciences, 2026)
This study examines the internalization of Islamic education values through halaqah at LDK Al-Izzah UIN Sumatera Utara and its role in shaping student character. Halaqah is an Islamic tarbiyah system that emphasizes character formation through habituation, exemplary practice, and continuous evaluation between murobbi and mutarobbi. This study uses a qualitative descriptive method. Data were collected through observation, interviews, and documentation, then analyzed using data reduction, display, and conclusion drawing.““The findings show that halaqah is conducted in structured small groups guided by a murobbi. The internalization process occurs through stages of value delivery, understanding, habituation, and reinforcement. Activities include aqidah, worship, moral education, and daily evaluation. A close tarbiyah relationship between murobbi and mutarobbi supports character development. The study finds improvements in worship discipline, moral behavior, and social responsibility. In conclusion, halaqah is an effective system for internalizing Islamic values and shaping student character.Keywords: halaqah, value internalization, Islamic education, murobbi, mutarobbi, character.